Cytoplasmatic domain of Na,K-ATPase α-subunit is responsible for the aggregation of the enzyme in proteoliposomes - Rigos, Carolina Fortes (2010)
We studied the thermal dependence of amide I′ infrared absorption and fluorescence emission of Trp residues in the Na,K-ATPase of rabbit kidney. We studied the whole enzyme solubilized with detergent, the whole enzyme reconstituted in proteoliposomes and the protein fraction that remained in the lipid membrane after the trypsin digestion of the proteoliposomes. Cooperative unfolding and aggregation with increasing temperature were observed in the whole protein, whether solubilized or reconstituted, but not in the fraction remaining after trypsinization. The protein influenced the physical state of the lipid, decreasing the temperature of the gel to liquid-crystalline phase transition and the degree of cooperativity. This study provides new information for the understanding of the processes controlling the association mechanisms that are important for enzyme function in natural membranes. © 2009 Elsevier B.V. All rights reserved.